Therapies for Cognitive Impairment and Neurological Protection - Hoyle, Brian (MD Conference Express, 2014)
This article discusses discussed cognitive impairment in relationship to multiple sclerosis (MS). Cognitive impairment is seen in >65% of patients in clinical studies of MS [Fischer JS et al. Ann Neurol. 2000]. The impairment has been documented in all subtypes and stages of MS [Amato MP et al. Neurology. 2010; Amato MP et al. Neurology. 2008; Potagas C et al. J Neurol Sci. 2008; Amato MP et al. J Neurol. 2006; Fischer JS et al. Ann Neurol. 2000].